2023
DOI: 10.3389/fpsyg.2023.986221
|View full text |Cite
|
Sign up to set email alerts
|

Ecological contexts associated with early childhood curiosity: Neighborhood safety, home and parenting quality, and socioeconomic status

Abstract: IntroductionCuriosity is an important social-emotional process underlying early learning. Our previous work found a positive association between higher curiosity and higher academic achievement at kindergarten, with a greater magnitude of benefit for children with socioeconomic disadvantage. Because characteristics of the early caregiving and physical environment impact the processes that underlie early learning, we sought to examine early environmental experiences associated with early childhood curiosity, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…Further research, particularly studies designed to investigate causal relationships and cross-cultural studies outside the United States, is needed. Additionally, a complementary research direction would be to explore potential confounders, such as intelligence (von Stumm & Plomin, 2015), or potential moderators, such as the capacity for higher SES people to create a more stable or secure environment, leading to heightened curiosity levels (Shah et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research, particularly studies designed to investigate causal relationships and cross-cultural studies outside the United States, is needed. Additionally, a complementary research direction would be to explore potential confounders, such as intelligence (von Stumm & Plomin, 2015), or potential moderators, such as the capacity for higher SES people to create a more stable or secure environment, leading to heightened curiosity levels (Shah et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this hypothesis, experimental research across many species, from honeybees to parrots to orangutans, has provided evidence that individuals in more resource-rich environments exhibit greater exploratory behaviors (e.g., Damerius et al, 2017; Forss et al, 2015; Katz & Naug, 2015; Mettke-Hofmann et al, 2002). In humans, some studies showed that familial socioeconomic levels or other factors of environmental quality were associated with higher levels of curiosity in kindergarten (Shah et al, 2023; see also: Xu et al, 2023), more creativity in elementary school children (Zhang et al, 2018), and heightened levels of openness in adolescence (Lloyd et al, 2022; see Oh et al, 2023, for longitudinal data; see Menardo et al, 2017, for a negative association between childhood adversity and exploration in a behavioral task). Data from the World Values Survey also demonstrate a strong correlation between a country’s gross domestic product per capita, a proxy for environmental affluence, and the average level of trait openness to change in this country: Individuals in higher gross domestic product societies tend to be more open to change (Korotayev et al, 2019).…”
mentioning
confidence: 99%
“…The natural propensity of individuals toward curiosity serves as a powerful driver of motivation (Mahama et al, 2023;Shah et al, 2023), forming a crucial area of investigation for psychologists and educational researchers exploring fundamental traits and personal attributes (Evans et al, 2023;Spitzer et al, 2023). However, curiosity research faces challenges arising from diverse vocabulary, operational definitions, and measuring methods, which have hindered its progress despite its widespread recognition among academic communities.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence regarding the role of maternal nutrition, breastfeeding, parenting skills, parent’s education, cultural practices, and intra-family relations on child development 3 , 6 . There is also ample evidence of associations between socioeconomic conditions of the family and child development 7 , 8 , 9 . For instance, maternal educational attainment is strongly associated with better child development: children of mothers with low educational level may have a slower physical and emotional development when compared with children of mothers with complete high-school or higher education 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%